Исследование алгоритмов обработки сигналов методом компьютерного моделирования - Свиридов, В. Э. (My University, 2018)
In this paper, we studied the algorithms for signal processing by computer simulation using signal quantization. The simulation of the algorithm for processing bursts of signals is performed, and the qualitative characteristics of the algorithm are investigated.
Keywords: обработка сигналов